PENGARUH KOMPOSISI MEDIA TANAM DAN KONSENTRASI EKSTRAK TAUGE TERHADAP PERTUMBUHAN AWAL STEK BIBIT VANILI (Vanila planifolia Andrews) - Dwi Erwin Kusbianto; Fitri Ramadhani; Hasbi Mubarak Suud; Setiyono Setiyono; Susan Barbara Patricia Meliala (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
Vanilla is one of the export commodities with a relatively high economic value. One of the problems with vanilla cultivation is the health of vanilla seedlings. This study aimed to determine the best concentration of growth regulators from bean sprout extract to vanilla seed cuttings with some variations of plant media. This research was conducted by observing changes in shoot length, root length, number of leaves, and root volume in plant samples due to providing various types of planting media treatments and PGR fertilization. This study was designed using the Completely Randomized Design method with two factors. The treatment composition of growing media with bean sprout extract concentration showed a significant effect on the growth parameters, which affected the observation parameters, including the number of leaves, shoot length, root length, and root volume. The best bean sprout extract concentration was 10%, and the best-growing media composition was soil and manure.